1999
DOI: 10.1021/jf9800256
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Evaluation of Virgin Olive Oil of First and Second Extraction

Abstract: Virgin olive oils from percolation (first extraction) have been compared with the corresponding oils from centrifugation (second extraction). The former were characterized by (i) higher contents of total phenols, o-diphenols, hydroxytyrosol, tyrosol-aglycons, tocopherols, trans-2-hexenal, total volatiles, and waxes; (ii) higher values of resistance to autoxidation and of turbidity; (iii) higher sensory scores; (iv) higher ratios of campesterol/stigmasterol, trans-2-hexenal/hexanal, and trans-2-hexenal/total vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 18 publications
3
78
0
1
Order By: Relevance
“…This may be a real difference due to olive variety or seasonal=climatic effects, or it may be an artefact due to methodological differences. Other studies have identified a range of atocopherol contents consistent with that identified in the present study (García et al, 1996;Gutiérrez et al, 1999;Ranalli et al, 1999a).…”
Section: Discussionsupporting
confidence: 90%
“…This may be a real difference due to olive variety or seasonal=climatic effects, or it may be an artefact due to methodological differences. Other studies have identified a range of atocopherol contents consistent with that identified in the present study (García et al, 1996;Gutiérrez et al, 1999;Ranalli et al, 1999a).…”
Section: Discussionsupporting
confidence: 90%
“…Espínola et al [11] and Kalua et al [18] also reported a presence of little influence on oil acidity with kneading temperature. Literature survey also showed that oils exhibiting higher acidity are obtained as a result of long kneading time at high temperature [16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…Kneading process at different temperature and time pairs makes the olive paste uniform and breaks up the oil/water emulsion. Changes in quality parameters such as free acid and peroxide value as a function of temperature, time, and maturity stage have been studied [14,15] Kneading conditions related changes in quality parameters are associated with an increase in lipase activity (responsible for free acidity increase) and an intensification of the primary oxidation processes (responsible for the increase of the peroxide value) [16][17][18][19]. As mentioned above, oil extraction in terms of yield performance and product's quality is under effects of many factors, but being in different extents.…”
Section: Introductionmentioning
confidence: 99%
“…In continuous cycles, metallic crushers that use hammer, disc and roller are used to mill the olives, and a decanter with a centrifuge, horizontally placed, is used for centrifugation of the paste. A vertical centrifuge is used to separate the oily paste into oil and water (Ranalli et al 1999). Extra-virgin olive oil is obtained from the first physical cold pressure of the olive paste and is rich in phenolic compounds (Visioli et al 1998).…”
Section: Effect Of Oil Extraction Processes On the Content Of Phenolimentioning
confidence: 99%